Draft Genome Sequence of the Entomopathogenic Bacterium Bacillus pumilus 15.1, a Strain Highly Toxic to the Mediterranean Fruit Fly Ceratitis capitata - García Ramón, Diana Carolina (2015)
We present the draft whole-genome sequence of the entomopathogenic Bacillus pumilus 15.1 strain that consists of 3,795,691 bp and 3,776 predicted protein-coding genes. This genome sequence provides the basis for understanding the potential mechanism behind the toxicity and virulence of B. pumilus 15.1 against the Mediterranean fruit fly.